Functional assessment of the hand: reproducibility, acceptability, and utility of a new system for measuring strength. Issue 3 (March 1987) - Helliwell, P; Howe, A; Wright, V
Abstract : A new system for measuring strength of the hand using a torsion dynamometer linked to a microprocessor is described. The system permits analysis of timed squeezes of both grip and pinch and is adjustable to all sizes of hand and degrees of hand deformity. Results obtained with the system were found to be reproducible, and the rigid device was acceptable to a group of patients with arthritic hands. In rheumatoid arthritis there is a marked reduction in maximum grip and pinch strength, together with a prolongation of the time taken to reach this maximum, and increased fatigue. The limitations of grip strength as a measure of function of the hand are discussed.